2014
DOI: 10.1111/1469-0691.12747
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for carbapenem-resistant Klebsiella pneumoniae bloodstream infection among rectal carriers: a prospective observational multicentre study

Abstract: Knowledge of carbapenem-resistant Klebsiella pneumoniae (CR-KP) colonization is important to prevent nosocomial spread but also to start prompt adequate antibiotic therapy in patients with suspicion of infection. However, few studies have examined the incidence and risk factors for CR-KP bloodstream infection (BSI) among rectal carriers. To identify risk factors for CR-KP BSI among carriers, we performed a multicentre prospective matched case-control study of all adult CR-KP rectal carriers hospitalized in fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
3
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 14 publications
(18 reference statements)
12
149
3
15
Order By: Relevance
“…As in ours, only a few studies have addressed progression to infection among colonized patients with CPE, using the recovery from clinical sites as a marker for infection. [6][7][8] Interestingly, our results were similar to these studies, mainly in relation to the incidence rate of infections among colonized patients and the predominance of KPC-2-KP among the CPE isolates. On the other hand, in these studies, no data on polymyxin B resistance was reported.…”
supporting
confidence: 90%
“…As in ours, only a few studies have addressed progression to infection among colonized patients with CPE, using the recovery from clinical sites as a marker for infection. [6][7][8] Interestingly, our results were similar to these studies, mainly in relation to the incidence rate of infections among colonized patients and the predominance of KPC-2-KP among the CPE isolates. On the other hand, in these studies, no data on polymyxin B resistance was reported.…”
supporting
confidence: 90%
“…For carbapenem-resistant Enterobacteriaceae, rectal colonization by resistant pathogens was followed by BSIs in 45% of neutropenic patients. 55 The association between colonization and subsequent infection has been reported for many MDR bacteria, such as VRE, ESBL-producing Enterobacteriaceae, P. aeruginosa, S. maltophilia and carbapenem or colistin resistant K. pneumoniae. 115,116 Therefore, decolonization before the onset of neutropenia seems appealing in case of carbapenem-resistant bacteria, but very few data on the efficacy of this approach exist in this setting.…”
Section: Othersmentioning
confidence: 98%
“…34 Of note, rectal colonization by carbapenem-resistant K. pneumoniae was followed by BSIs in 45% of neutropenic patients. 55 Also non-fermenting GN rods harbor frequently this type of resistance. In fact, P. aeruginosa, which is responsible for 15-20% of GN infections, 56 might be frequently carbapenem-resistant in some regions, as demonstrated in an Italian multicenter cohort, where 71% of strains were MDR.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
“…3,4,7,8 In a recent survey in a tertiary teaching Italian hospital, when compared to internal medicine patients (4.3/1000 colonization days), the highest incidence of CRKp infections among colonized patients was observed in hematology (26.3; P=0.04) and ICU (13.1; P=0.0004), followed by surgery (8.6; P=0.14), transplant (7.4; P=0.34), and long-term care (4.7; P=0.99). CRKp attributable mortality was highest in hematology (75%) followed by ICU (11%), transplant (7%), long term care (5%), internal medicine and surgery (both 2%).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Corrado Girmenia, 1 Claudio Viscoli, 2 Alfonso Piciocchi, 3 Laura Cudillo, 4 Stefano Botti, 5 Antonio Errico, 6 Loredana Sarmati, 7 Fabio Ciceri, 8 Franco Locatelli, 9 Maddalena Giannella, 10 Matteo Bassetti, 11 Carlo Tascini, 12 Letizia Lombardini, 6,13 Ignazio Majolino, 14 Claudio Farina, 15 Francesco Luzzaro, 16 Gian Maria Rossolini, [17][18][19] and …”
Section: F E R R a T A S T O R T I F O U N D A T I O Nunclassified